PANDANGAN EKONOMI ISLAM TERHADAP PERUBAHAN NILAI TUKAR UANG - Bayu firmansyah; Yola Amelda Putri; Wandrizal Wandrizal (Jurnal Ekonomi Sakti, 2023)
Changes in exchange rates are an urgent matter because exchange rates are not fixed from time to time and are not permanent. In economic theory, one can reduce and increase the quantity of money if pursued fairly, because without one's efforts, it cannot develop by itself. In the Islamic economic system currency exchange is still a matter of controversy because the circulating exchange rate is still changing. Likewise the implications of changes in exchange rates, which have principles that need to be reviewed from an Islamic economic perspective. Based on the results of the discussion, the literature states: (1) the exchange rate in Islamic economics is an element of an activity that is permitted. The exchange of currency between the same country or different countries should be in accordance with the provisions of the Islamic economy, (2) the implementation of changes in currency exchange rates does not only affect the level of local products but also affects the value of a country's currency, therefore deflation and inflation cannot be avoided. The implication of this exchange rate change that our nation is looking for is that currency chaos permeates Indonesia and other countries in Asia. The economy collapsed due to changes in currency exchange rates, causing the price of both local and foreign goods to increase. (3) in the Islamic economic order, the conception of the value of time is not money, but the future which has economic rates, not money which has a time value.